KARAKTERISTIKMINYAKATSIRI DARIDAUN TANAMANPUCUKMERAH (SyzygiumcampanulatumKorth.) - Fahrul Rozi Sembiring; Rudianda Sulaeman; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research is aimed to know the characteristic of essential oil produced from distillation process of pucuk merah leaves. The young leaves and old leaves of pucuk merah was distilled using distillation clevenger type. Then, it is done an observation of essential oil yield, the essential oil colour, essential oil scent and solubility in ethanol. The results showed that the yield of pucuk merah young leaves essential oil is much more than the pucuk merah old leaves essential oil which are each respectively 0,18% and 0,118%. The colour of essential oil from pucuk merah young leaves and old leaves pucuk merah is yellow. Then, the essential oil from pucuk merah leaves is soluble in ethanol PA at ratio 1:1. Furthermore, through panelists assessment it’s known the essential oil of young leaves has distinctive scent of pucuk merah than the essential oil of pucuk merah old leaves. As 65% panelists said that the essential oil from pucuk merah young leaves has distinctive scent of pucuk merah, while the others 35% said that it doesn’t have. For the essential oil from the old leaves, as 50% panelists said that the essential oil from pucuk merah old leaves has the distinctive scent of pucuk merah, while the others 50% panelists said that it doesn’t have. Keywords: Pucuk merah, Syzygium campanulatum Korth., Essential oil